Multiple Psychopharmacological Effects of the Traditional Japanese Kampo Medicine Yokukansan, and the Brain Regions it Affects - Mizoguchi, Kazushige; Ikarashi, Yasushi (Frontiers in Pharmacology, 2017)
The traditional Japanese Kampo medicine yokukansan (YKS) has indications for use in night crying and irritability in children, as well as neurosis and insomnia. It is currently also used for the treatment of the behavioral and psychological symptoms of dementia (BPSD) such as aggressiveness, agitation, and hallucinations. In parallel with clinical evidence, a significant amount of basic research has been undertaken to clarify the neuropsychopharmacological efficacies and mechanisms of YKS, with approximately 70 articles, including our own, being published to date. Recently, we reviewed the neuropharmacological mechanisms of YKS, including its effects on glutamatergic, serotonergic, and dopaminergic neurotransmission, and pharmacokinetics of its active ingredients. The purpose of this review is to integrate the information regarding the psychopharmacological effects of YKS with the brain regions known to be affected, to facilitate our understanding of the clinical efficacy of YKS. In this review, we first show that YKS has several effects that act to improve symptoms that are similar to BPSDs, like aggressiveness, hallucinations, anxiety, and sleep disturbance, as well as symptoms like tardive dyskinesia and cognitive deficits. We next show the evidence showing that YKS can interact with various brain regions, including the cerebral cortex, hippocampus, striatum, and spinal cord, dysfunctions of which are related to psychiatric symptoms, cognitive deficits, abnormal behaviors, and dysesthesia. In addition, the major active ingredients of YKS, geissoschizine methyl ether and 18β-glycyrrhetinic acid, are shown to predominantly bind to the frontal cortex and hippocampus, respectively. Our findings suggest that YKS has multiple psychopharmacological effects, and that these are probably mediated by interactions among several brain regions. In this review, we summarize the available information about the beneficial effects of YKS, a multicomponent Kampo medicine, on complex neural networks.